Omicron Variant and Infection Control in Pediatric Surgery Department - Aygün, Pakize; Kanan, Nevin (Cerrahpaşa Medical Journal, 2022)
Since the beginning of the COVID-19 pandemic, approaches in terms of the course of the disease in children and recommendations for approach in pediatric surgery are generally presented with limited data. Recently, the new wave in the pandemic caused by the Omicron variant raises new questions due to the transmission kinetics and the different clinical features. The World Health Organization and the United States Centers for Disease Control and Prevention have new recommendations on the prevention of the spread of COVID-19 in health institutions. Apart from the continuation of the World Health Organization’s routine recommendations, the use of respirators (N-95/FFP-2) is recommended in the emergency room, intensive care units, and units caring for COVID-19 patients, even when aerosol-generating procedures are not performed. United States Centers for Disease Control and Prevention, on the other hand, recommends reducing the isolation period to 7 days or even 5 days with a negative polymerase chain reaction test in vaccinated, asymptomatic health-care workers and cancelling post-contact quarantine practice. The Ministry of Health has also made arrangements in accordance with these recommendations. Current publications on infection control methods recommended in the field of pediatric surgery were reviewed in this study. Omicron spread can be prevented when the recommendations that can be applied in pediatric surgery clinics are taken into account. It is recommended to contact the Hospital Infection Control Committee regarding the implementation of COVID-19 precautions, the completion of the vaccination with the recommended dose in health-care workers, the arrangement of working and surgery hours, polymerase chain reaction scanning, and how the applications will be made. Mask–distance–hygiene and vaccination applications should be continued. Cite this article as: Aygün P, Kanan N. Omicron variant and infection control in pediatric surgery department. Cerrahpaşa Med J. 2022;46(3):269-271.